Medicinal and biological significance of quinazoline a highly important scaffold for drug discovery: A review - Vijaychand.A; S.N.Manjula; Bharath .E. N; Divya.B (International Journal of Pharma and Bio Sciences, 2011)
This article outlines the medicinal and biological significance of one of the most important heterocycles, the quinazoline. Quinazoline is a highly active scaffold exhibiting wide variety of medicinal and biological activities. An attempt is made in this article to cover the medicinally active compounds, along with the recent discoveries, which were reported to posses various biological activities. This is might be helpful in the development of these novel lead molecules to potential drug candidates.